Regularities of radiation and heterogeneous processes in contact of Zr and Zr1%Nb alloy with water - Agayev, T.N.; Faradj-zadeh, I.A.; Aliyev, A.G.; Eyubov, K.T.; Aliyev, S.M. (Вопросы атомной науки и техники, 2017)
Influence of radiation in the processes of hydrogen accumulation and zirconium oxidation as a result of heterogeneous processes in contact of zirconium and a Zr1%Nb alloy with water vapors is investigated. The contribution of radiation processes in these contacts on radiolysis and thermic radiolysis processes of water decomposition is revealed. It is established that radiation processes in contact of zirconium materials with water cause acceleration of molecular hydrogen accumulation processes, as a result of protective oxide film formation on a surface, and destructive oxidation.